(untitled) (Tzintzun, Revista de Estudios Históricos, 2016)
The paper makes an analysis of the irst road formation in the colonial era in Michoacán, from its prehispanic origins until the decade of 1560. It describes how the prehispanic routes contributed to colonial expansion and how Michoacán incorporated gradually a colonial network of roads that would exceed their original prehispanic limits. With this development, the original roads experienced a process of enlargement through the introduction of new forms of animal transport, a transcendent event in the analysis of the transformation of roads.